Strategi Bauran Pemasaran Wedding Package untuk Meningkatkan Jumlah Penyelenggaraan Wedding Event di Discovery Kartika Plaza Hotel - I Nyoman Sukana Sabudi; I Nengah Wirata; Endro Cahyadi (JURNAL BISNIS HOSPITALITI, 2020)
The target of wedding events at Discovery Kartika Plaza Hotel in 2018 and 2019 cannot be achieved. The right marketing mix strategy of wedding package can be used to increase the number of wedding events. This research used documentation study methods as well as interviews. Then use qualitative descriptive data analysis techniques to be analyzed using SWOT matrix analysis with 4P marketing mix (product, price, place and promotion). SWOT analysis compares between external factors that are opportunities and threats with internal factors that are strengths and weaknesses that produce four alternative components of strategy namely SO, ST, WO, and WT. Based on the research that has been done, Discovery Kartika Plaza Hotel offers wedding ceremony package and supported with 5 wedding dinner venues with outdoor concept in the form of garden beach view and has 1 ballroom but does not have chapel as an attraction. Wedding package prices offered to prospective couples are quite competitive with competitors but do not yet have prices for weekdays, weekends, low season and high season which are considered quite detrimental. It has two kinds of distribution channels namely direct distribution (internet, social media, telephone, and e-mail) and indirect distribution through third parties.